Answer:
the answer would be 2(x - 3) = 22 (C)
Explanation:
step 1:
2(x - 3) = 22
step 2: divide both sides by the equation 2
x - 3 = 11
step 3: move constant (3) to the right and change its sign
x = 11 + 3
step 4: add the numbers (11 and 3)
x = 14
C
Simply plug in x for all the questions to see if the x is the solution
A.) 3(20-14) = 44
3(16)=48
so A is incorrect
B.) 3(12-14) = 6
3(-2) = -6
so B is incorrect
C.) 2(14-3) =22
2(11) =22
C is correct
D.) 2(14)-3=22
28-3 = 25
so D is incorrect
5.6m questions
7.3m answers